Ultrahigh drive current and large selectivity in GeS selector - Shujing Jia (Nature Portfolio, 2020)
Designing efficient selector devices for large-scale nonvolatile memory and neuromorphic array systems remains a challenge. Here, the authors propose a two-terminal ovonic threshold switching selector device with a large drive current density and a high nonlinearity, capable emulating stochastic integrate-and-fire neuron behavior.